Foucault, Politics, and Violence. Issue 2 (1st November 2013) - McCall, Corey
Abstract Oksala's book is the latest in a series of attempts to examine Foucault's work during the late 1970s. We can delineate two clear trends in recent Foucault scholarship on this period: the first trend provides analyses and evaluations of this period while asecond trend attempts to apply Foucault's analyses of these key concepts to contemporary society. Oksala's book attempts to do both, although if forced to choose one would have to place it more firmly in the first camp than the second. Accordingly, the first section of this review essay situates Oksala's book within this recent context. I discuss her analysis and reconstruction of Foucault's late 1970s work before turning in the final section to the various ways that she applies this analysis to current legal and political debates.